Temporal Linkages in Violent and Nonviolent Criminal Activity - Brame, Robert W. (Journal of quantitative criminology, 2005)
Research on the temporal distribution of criminal behavior has highlighted two distinct mechanisms—population heterogeneity and state dependence. Most of this work indicates that long-term patterns of criminal offending reflect a mixture of stable individual differences and the causal effect of life events and experiences. Yet several ambiguities remain. Among the most important of these problems is whether both population heterogeneity and state dependence processes operate for different types of offending. We use longitudinal official record and self-report data for violent and non-violent offending activity from the Rochester Youth Development Study to address these ambiguities.